Disparities in Utilization of Psychiatry Services Among Home Care Clients: The Tale of Two Canadian Jurisdictions - Poss, Jeffrey; Mitchell, Lori; Mah, Jasmine; Keefe, Janice (Frontiers in Psychiatry, 2021)
Publicly funded home care in Canada supports older adults in the community to delay institutional care, which results in complex care populations with multimorbidity that includes mental health problems. The purpose of this study is to examine prevalence of psychiatric diagnoses and other mental health symptoms among older clients in two publicly funded Home Care (HC) Programs and their psychiatry service utilization (psychiatrist visits) after being admitted to home care. This retrospective cohort study examines clients age 60 years and older in the two Canadian provinces of Manitoba (MB), specifically the Winnipeg Regional Health Authority (WRHA) (n = 5,278), and Nova Scotia (NS) (n = 5,323). Clients were admitted between 2011 and 2013 and followed up to 4 years. Linked data sources include the InterRAI Resident Assessment Instrument for Home Care (RAI-HC), physician visit/billing data and hospital admission data. Both regions had similar proportions (53%) of home care clients with one or more psychiatric diagnoses. However, we observed over 10 times the volume of psychiatry visits in the WRHA cohort (8,246 visits vs. 792 visits in NS); this translated into a 4-fold increased likelihood of receiving psychiatry visits (17.2% of WRHA clients vs. 4.2% of NS clients) and 2.5 times more visits on average per client (9.1 avg. visits in MB vs. 3.6 avg. visits in NS). The location of psychiatry services varied, with a greater number of psychiatry visits occurring while in hospital for WRHA HC clients compared to more visits in the community for NS HC clients. Younger age, psychotropic medication use, depressive symptoms, dementia, and having an unstable health condition were significantly associated with receipt of psychiatry visits in both cohorts. Access to psychiatric care differed between the cohorts despite little to no difference in need. We conclude that many home care clients who could have benefitted from psychiatrist visits did not receive them. This is particularly true for rural areas of NS. By linking the RAI-HC with other health data, our study raises important questions about differential access to psychiatry services by site of care (hospital vs. community), by geographical location (MB vs. NS and urban vs. rural) and by age. This has implications for staff training and mental health resources in home care to properly support the mental health needs of clients in care. Study results suggest the need for a mental health strategy within public home care services.